Using side channels in remote procedure calls to return information in an interactive environment (2020)
Systems and methods for exchanging information in a distributed computing system implementing an interactive application, such as a location-based parallel reality game, are provided. In particular, the subject matter of the present disclosure provides an alternative approach for providing and processing return results from a remote procedure call (RPC) by which remote computing systems (e.g. a game server and a remote client) send requests and responses to one another. Rather than providing a single return result in response to a single request as in typical remote procedure calls, information about updates to the state of the interactive application, such as updates to game status, can be returned via side channels which are handled generically while passing the main return result of the invoked service directly back to the caller.